Oficinas pedagógicas como estratégia para a promoção da saúde na formação docente continuada - Visintainer, Daniela Sastre Rossi (2018)
This study is an action research developed in a state public school, in which the health promotion was used to contextualize the continuing teacher education process. Fourteen teachers from different areas teaching in the last years of elementary school participated on this study. The objective was to analyze the contribution of the health promotion workshops in the pedagogical practice and professional development. The participant observation, the board diary, questionnaires with open questions and semi-structured interviews were used for data records, that were analyzed according to their content. The study was organized into three workshop cycles during three consecutive years. In the first cycle, the workshops focused the instrumentalization, study and reflection about themes related to the students' health promotion, such as body image, physical activity and nutrition. Teachers were able to think about ways to approach the subjects along with their disciplinary contents and believe that their approach promotes greater significance of the school contents. In the second cycle of workshops, the objective was to encourage the construction and development of teaching-learning actions contextualized with health promotion. Teachers developed three individual learning projects and one interdisciplinary project. They observed that the contextualization, in fact, promotes greater meaning and understanding of the contents, besides arousing students' interest and motivation, and promote autonomy and behavior changing. Learning projects presented obstacles, such as lack of time in comparison to the other requirements of the curriculum, initial resistance of the students, lack of support and resistance of some teachers, among other difficulties, but they did not obstruct its progress. Although only an interdisciplinary project has been developed, most teachers consider it advantageous for learning, because it establishes greater relationships between different contents and reality, and enriches interpersonal relationships and social interactions, however, the obstacles are significant. In the third cycle, the workshops aimed to promote reflection about pedagogical practice through scientific writing based on their contextualized pedagogical practices. Teachers produced articles and abstracts, transcribed their practices and presented them in a scientific event, one of them was published in a journal. The writing process promoted the evaluation of the pedagogical practices, the perception of difficulties and needs, the incorporation of new learning teaching strategies and assumptions such as contextualization, and encouraged the innovations and the teacher motivation. As a participative, constructive and reflexive space, the workshops contributed to the development of health promotion actions at school and pedagogical knowledge production. However, interdisciplinary practice is still a challenge for most teachers, who claimed the lack of time to build and develop integrated activities.